International Comparisons and Transfer of Labour Market Institutions - Wolfgang Ochel (Center for Economic Studies and ifo Institute (CESifo), 2002)
International comparisons of labour market institutions and their transfer across boundaries have gained in importance. The paper deals with the question of the best way to proceed in making such comparisons. At the same time the question of the possibilities and limits to institutional transfer is addressed. On the one hand competition between systems obliges governments to adopt institutions of other countries. On the other hand inflexibilities resulting from path dependency and/or powerful domestic interest groups can impede the transfer of institutions.
Keywords: 330